Heidi - Spyri, Johanna (New York Watermill press, 1980)
When an aunt drops five-year-old Heidi off to live with her grandfather in the Alps-the two of them alone in a small hut on a hill-she's initially very lonely. Soon, however, she comes to appreciate her new, simple life; she loves walking through the pastures with her friend Peter the goatherd and spending quiet time with her grandfather. Three years later, Heidi's aunt returns to take her to the town to become a companion for Clara, a sick little girl of a wealthy family. But even though Heidi bonds with Clara and brings new life to the household, she becomes more and more homesick and wants desperately to return to her grandfather.
Keywords: Tham khảo